Transparent electroconductive film

JP2025024115AInactive Publication Date: 2025-02-19NITTO DENKO CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024200790
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-09-17
Filing Date
2024-11-18
Publication Date
2025-02-19
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure 2025024115000001_ABST
    Figure 2025024115000001_ABST
Patent Text Reader

Abstract

To provide a transparent electroconductive film featuring superior corrosion resistance and high infrared reflectivity.SOLUTION: A transparent electroconductive film 1 comprises a substrate 2 and a crystalline transparent electroconductive layer 3 in order toward one side in the thickness direction. The crystalline transparent electroconductive layer 3 contains a rare gas having a larger atomic number than argon. The crystalline transparent electroconductive layer 3 has a carrier density of 13.0×1020( / cm3) or higher.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transparent conductive film. [Background technology]

[0002] 2. Description of the Related Art A transparent conductive film is known that includes a substrate, a first inorganic oxide layer, a metal layer, and a second inorganic oxide layer in that order on one side in the thickness direction (see, for example, Patent Document 1 below). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 05-334924 Summary of the Invention [Problem to be solved by the invention]

[0004] Transparent conductive films are sometimes used for long periods under high temperature and high humidity conditions, and even in such cases, they are required to have high corrosion resistance.

[0005] Depending on the application and purpose, the transparent conductive film is required to have a higher reflectance to infrared rays.

[0006] The present invention provides a transparent conductive film that has excellent corrosion resistance and high infrared reflectance. [Means for solving the problem]

[0007] The present invention (1) comprises a substrate and a crystalline transparent conductive layer in this order toward one side in a thickness direction, the crystalline transparent conductive layer containing a rare gas having an atomic number larger than that of argon, and the carrier density of the crystalline transparent conductive layer is 13.0×10 20 ( / cm 3 ) or more.

[0008] This transparent conductive film has a crystalline transparent conductive layer instead of the metal layer described in Patent Document 1, and therefore has excellent corrosion resistance.

[0009] In addition, the carrier density of the crystalline transparent conductive layer of this transparent conductive film is 13.0 × 10 20 ( / cm 3 ), the amount of carriers that can contribute to the reflection of infrared rays is large. Therefore, the reflectance of infrared rays is high.

[0010] The present invention (2) includes the transparent conductive film according to (1), in which the crystalline transparent conductive layer is an inorganic oxide layer. Effect of the Invention

[0011] The transparent conductive film of the present invention has excellent corrosion resistance and high infrared reflectance. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a cross-sectional view of one embodiment of a transparent conductive film of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of a transparent conductive film of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] 1. Transparent conductive film 1 A transparent conductive film 1 according to one embodiment of the present invention will be described with reference to Fig. 1. This transparent conductive film 1 extends in a planar direction, which is perpendicular to the thickness direction.

[0014] 1.1 Layer structure of transparent conductive film 1 The transparent conductive film 1 includes a substrate 2 and a crystalline transparent conductive layer 3, which are arranged in this order toward one side in the thickness direction. That is, in this transparent conductive film 1, the substrate 2 and the crystalline transparent conductive layer 3 are arranged in this order toward one side in the thickness direction. In this embodiment, the transparent conductive film 1 includes only the substrate 2 and the crystalline transparent conductive layer 3.

[0015] 1.2 Base material 2 In this embodiment, the substrate 2 forms the other surface in the thickness direction of the transparent conductive film 1. The substrate 2 improves the mechanical strength of the transparent conductive film 1. The substrate 2 extends in the planar direction.

[0016] 1.2.2 Layer structure of substrate 2 In this embodiment, the substrate 2 includes a substrate sheet 21 and a functional layer 20 in this order in the thickness direction. In this embodiment, the functional layer 20 is a multilayer. The functional layer 20 contacts one side and the other side of the substrate sheet 21 in the thickness direction. The functional layer 20 preferably includes an optical adjustment layer 22 and a hard coat layer 23. In this embodiment, the substrate 2 preferably includes an optical adjustment layer 22, a substrate sheet 21, and a hard coat layer 23 in this order toward the other side in the thickness direction.

[0017] 1.2.2.1 Base sheet 21 The base sheet 21 has flexibility. The base sheet 21 may be, for example, a resin film. The resin in the resin film is not limited. Examples of the resin include polyester resin, acrylic resin, olefin resin, polycarbonate resin, polyethersulfone resin, polyarylate resin, melamine resin, polyamide resin, polyimide resin, cellulose resin, polystyrene resin, and norbornene resin. As the resin, preferably, polyester resin is used from the viewpoints of transparency and mechanical strength. Examples of polyester resins include polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate, and preferably, PET.

[0018] The thickness of the base sheet 21 is preferably 1 μm or more, more preferably 10 μm or more, and even more preferably 30 μm or more. The thickness of the base sheet 21 is preferably 300 μm or less, more preferably 200 μm or less, even more preferably 150 μm or less, and particularly preferably 100 μm or less. The ratio of the thickness of the base sheet 21 to the thickness of the base material 2 is, for example, 80% or more, preferably 95% or more, and, for example, 100% or less, preferably 99% or less.

[0019] 1.2.2.2 Optical adjustment layer 22 The optical adjustment layer 22 makes the pattern shape of the crystalline transparent conductive layer 3 difficult to be visually recognized. The optical adjustment layer 22 is disposed on one surface of the base sheet 21 in the thickness direction. The optical adjustment layer 22 contacts one surface of the base sheet 21 in the thickness direction. The optical adjustment layer 22 is, for example, a cured product layer of a curable composition (first curable composition) containing a curable resin. Examples of the curable resin include acrylic resin, urethane resin, amide resin, silicone resin, epoxy resin, and melamine resin. In this embodiment, the cured product layer preferably does not contain particles. The refractive index of the optical adjustment layer 22 is, for example, 1.40 or more, preferably 1.55 or more, and, for example, 1.80 or less, preferably 1.70 or less. The thickness of the optical adjustment layer 22 is, for example, 5 nm or more, preferably 10 nm or more, and, for example, 200 nm or less, preferably 100 nm or less. The ratio of the thickness of the optical adjustment layer 22 to the thickness of the substrate 2 is, for example, 0.01% or more, preferably 0.1% or more, and for example, 2% or less, preferably 1% or less.

[0020] 1.2.2.3 Hard Coat Layer 23 The hard coat layer 23 makes it difficult for scratches to form on one side of the crystalline transparent conductive layer 3 in the thickness direction when the transparent conductive film 1 is wound to prepare a roll body. The hard coat layer 23 is disposed on the other side of the substrate sheet 21 in the thickness direction. The hard coat layer 23 contacts the other side of the substrate sheet 21 in the thickness direction. The hard coat layer 23 is, for example, a cured layer of a curable composition (second curable composition) containing particles and a curable resin. Examples of the particles include oxide particles, glass particles, and organic particles. Examples of the oxide particles include silica particles, alumina particles, titania particles, zirconia particles, calcium oxide particles, tin oxide particles, indium oxide particles, cadmium oxide particles, and antimony oxide particles. Examples of the material of the organic particles include polymethyl methacrylate particles, polystyrene particles, polyurethane particles, acrylic-styrene copolymer particles, benzoguanamine particles, melamine particles, and polycarbonate particles. The curable resin may be the curable resin contained in the first curable composition. The thickness of the hard coat layer 23 is, for example, 0.1 μm or more, preferably 0.5 μm or more, and for example, 10 μm or less, preferably 3 μm or less. The ratio of the thickness of the hard coat layer 23 to the thickness of the substrate 2 is, for example, 0.1% or more, preferably 2% or more, and for example, 10% or less, preferably 5% or less.

[0021] The thickness of the functional layer 20 is, for example, 0.15 μm or more, and, for example, 3.5 μm or less. The thickness of the functional layer 20 is the total thickness of the optical adjustment layer 22 and the hard coat layer 23. The ratio of the thickness of the functional layer 20 to the thickness of the substrate sheet 21 is, for example, 0.01 or more, preferably 0.02 or more, and, for example, 0.10 or less, preferably 0.05 or less. The ratio of the thickness of the functional layer 20 to the thickness of the substrate 2 is, for example, 1% or more, preferably 2% or more, and, for example, 10% or less, preferably 5% or less.

[0022] 1.2.3 Thickness of substrate 2 The thickness of the substrate 2 is, for example, 5 μm or more, preferably 10 μm or more, more preferably 25 μm or more, and, for example, 500 μm or less, preferably 200 μm or less, more preferably 100 μm or less. The thickness of the substrate 2 is the total thickness of the substrate sheet 21, the optical adjustment layer 22, and the hard coat layer 23.

[0023] 1.2.4 Physical properties of substrate 2 The total light transmittance of the substrate 2 is, for example, 75% or more, preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. The upper limit of the total light transmittance of the substrate 2 is not limited. The upper limit of the total light transmittance of the substrate 2 is, for example, 100% or less. The total light transmittance of the substrate 2 is determined based on JIS K 7375-2008. The total light transmittance of the following members is determined based on the same method as above.

[0024] A commercially available product can be used as the base material 2. An example of a commercially available product is GF-50JBN (manufactured by Mitsubishi Chemical Corporation).

[0025] 1.3 Crystalline transparent conductive layer 3 In this embodiment, the crystalline transparent conductive layer 3 is preferably referred to as an infrared reflective layer (or an infrared cut layer). Infrared rays include light (electromagnetic waves) with a wavelength of at least 1500 nm, and specifically, light with a wavelength of 800 nm or more and 1 mm or less.

[0026] The crystallinity of the transparent conductive layer is determined, for example, by immersing the transparent conductive layer in hydrochloric acid (20°C, concentration 5% by mass) for 15 minutes, followed by rinsing and drying, and then measuring the resistance between terminals about 15 mm from one side of the transparent conductive layer. If the resistance between terminals (resistance between two terminals) between 15 mm of the transparent conductive layer after the immersion, rinsing and drying is 10 kΩ or less, the transparent conductive layer is crystalline (i.e., crystalline transparent conductive layer 3), whereas if the resistance exceeds 10 kΩ, the transparent conductive layer is amorphous (i.e., amorphous transparent conductive layer 31).

[0027] In this embodiment, the crystalline transparent conductive layer 3 forms one surface of the transparent conductive film 1 in the thickness direction. The crystalline transparent conductive layer 3 is disposed on one surface of the substrate 2 in the thickness direction. The crystalline transparent conductive layer 3 contacts one surface of the substrate 2 in the thickness direction. In this embodiment, the crystalline transparent conductive layer 3 contacts one surface of the optical adjustment layer 22 (functional layer 20) in the thickness direction.

[0028] 1.3.1 Carrier density of the crystalline transparent conductive layer 3 The carrier density of the crystalline transparent conductive layer 3 is 13.0×10 20 ( / cm 3 )That's all.

[0029] On the other hand, the carrier density of the crystalline transparent conductive layer 3 is 13.0×10 20 ( / cm 3 ), the amount of carriers that contribute to the reflection of infrared rays in the crystalline transparent conductive layer 3 is insufficient.

[0030] Therefore, the crystalline transparent conductive layer 3 does not sufficiently reflect infrared light, and as a result, the reflectance of the transparent conductive film 1 to infrared light decreases.

[0031] On the other hand, in the present invention, the carrier density of the crystalline transparent conductive layer 3 is 13.0×10 20 ( / cm 3 ), there is a sufficient amount of carriers that contribute to the reflection of infrared rays in the crystalline transparent conductive layer 3. Therefore, the crystalline transparent conductive layer 3 sufficiently reflects infrared rays, and as a result, the reflectance of the transparent conductive film 1 to infrared rays is high.

[0032] The carrier density of the crystalline transparent conductive layer 3 is preferably 13.2×10 20 ( / cm 3 ) or more, more preferably 14.0×10 20 ( / cm 3 ) or more, more preferably 15.0×10 20 ( / cm 3 ) or more, particularly preferably 16.0×10 20 ( / cm 3) or more, most preferably 16.7×10 20 ( / cm 3 ) or more, and even more, 17.0×10 20 ( / cm 3 ) or more, and even more, 18.0×10 20 ( / cm 3 ) or higher is preferable.

[0033] The upper limit of the carrier density of the crystalline transparent conductive layer 3 is not limited. The upper limit of the carrier density of the crystalline transparent conductive layer 3 is, for example, 50.0×10 20 ( / cm 3 ), and even 40.0×10 20 ( / cm 3 ), and even 30.0×10 20 ( / cm 3 ).

[0034] The carrier density of the crystalline transparent conductive layer 3 is adjusted, for example, by the method and conditions for forming the crystalline transparent conductive layer 3. When the crystalline transparent conductive layer 3 is formed by reactive sputtering, preferably, the amount of reactive gas introduced is reduced and / or the sputtering gas contains a rare gas having an atomic number higher than that of argon. More preferably, the amount of reactive gas introduced is reduced and the sputtering gas contains a rare gas having an atomic number higher than that of argon.

[0035] The carrier density of the crystalline transparent conductive layer 3 is determined using a Hall effect measurement system.

[0036] 1.3.2 Material, thickness and other physical properties of the crystalline transparent conductive layer 3 Examples of materials for the crystalline transparent conductive layer 3 include inorganic oxides, and preferably metal oxides. The metal oxides include at least one metal selected from the group consisting of In, Sn, Zn, Ga, Sb, Nb, Ti, Si, Zr, Mg, Al, Au, Ag, Cu, Pd, and W. Specifically, examples of materials for the crystalline transparent conductive layer 3 include indium zinc composite oxide (IZO), indium gallium zinc composite oxide (IGZO), indium gallium composite oxide (IGO), indium tin composite oxide (ITO), and antimony tin composite oxide (ATO), and preferably indium tin composite oxide (ITO) from the viewpoint of improving crack resistance.

[0037] The content of tin oxide (SnO2) in the indium tin composite oxide is, for example, 0.5 mass% or more, preferably 3 mass% or more, more preferably 6 mass% or more, and for example, less than 50 mass%, preferably 25 mass% or less, more preferably 15 mass% or less.

[0038] The crystalline transparent conductive layer 3 contains a rare gas having an atomic number greater than that of argon. In this embodiment, the crystalline transparent conductive layer 3 preferably contains a rare gas having an atomic number greater than that of argon, but does not contain argon.

[0039] In the first step described below, when the sputtering gas contains argon, a large amount of argon is taken into the crystalline transparent conductive layer 3. In contrast, in the present embodiment, in which the sputtering gas contains a rare gas with a higher atomic number than argon and does not contain argon, the crystalline transparent conductive layer 3 is prevented from taking in a large amount of sputtering gas. Therefore, the crystalline transparent conductive layer 3 becomes dense, and as a result, the carrier density of the crystalline transparent conductive layer 3 becomes high.

[0040] Specifically, the crystalline transparent conductive layer 3 is an inorganic oxide (preferably a metal oxide) containing a rare gas having an atomic number greater than that of argon. In other words, the crystalline transparent conductive layer 3 is a composition in which a rare gas having an atomic number greater than that of argon is mixed into an inorganic oxide (preferably a metal oxide). The crystalline transparent conductive layer 3 preferably does not contain an elemental metal.

[0041] Examples of rare gases having an atomic number greater than that of argon include krypton, xenon, and radon. These can be used alone or in combination. Preferred rare gases having an atomic number greater than that of argon include krypton and xenon, and more preferably, krypton (Kr) is used from the viewpoints of low cost and excellent electrical conductivity.

[0042] The method for identifying the rare gas is not limited. For example, the rare gas having an atomic number larger than that of argon in the crystalline transparent conductive layer 3 is identified by Rutherford Backscattering Spectrometry, secondary ion mass spectrometry, laser resonance ionization mass spectrometry, and / or X-ray fluorescence analysis.

[0043] The content of the rare gas having an atomic number larger than that of argon in the crystalline transparent conductive layer 3 is, for example, 0.0001 atom% or more, preferably 0.001 atom% or more, and for example, 1.0 atom% or less, more preferably 0.7 atom% or less, even more preferably 0.5 atom% or less, particularly preferably 0.3 atom% or less, particularly preferably 0.2 atom% or less, and most preferably 0.15 atom% or less. If the content of the rare gas having an atomic number larger than that of argon in the crystalline transparent conductive layer 3 is within the above range, the reflectance of the crystalline transparent conductive layer 3 to infrared rays can be increased.

[0044] The lower limit of the content is the ratio corresponding to the case where the presence of a rare gas having an atomic number greater than that of argon can be confirmed by a fluorescent X-ray analyzer, and is at least 0.0001 atomic %.

[0045] The thickness of the crystalline transparent conductive layer 3 is, for example, 15 nm or more, preferably 35 nm or more, more preferably 50 nm or more, even more preferably 75 nm or more, particularly preferably 100 nm or more, and particularly preferably 120 nm or more. The thickness of the crystalline transparent conductive layer 3 is, for example, 500 nm or less, preferably 300 nm or less, more preferably 200 nm or less.

[0046] The total light transmittance of the crystalline transparent conductive layer 3 is, for example, 75% or more, preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. There is no upper limit to the total light transmittance of the crystalline transparent conductive layer 3. The upper limit of the total light transmittance of the crystalline transparent conductive layer 3 is, for example, 100%.

[0047] The surface resistance of the crystalline transparent conductive layer 3 is, for example, 300Ω / □ or less, preferably 100Ω / □ or less, more preferably 14Ω / □ or less, even more preferably 10.5Ω / □ or less, particularly preferably 10.1Ω / □ or less, and most preferably 10.0Ω / □ or less. The surface resistance of the crystalline transparent conductive layer 3 is, for example, 0.1Ω / □ or more, preferably 1Ω / □ or more. The resistivity is measured by a four-terminal method.

[0048] 1.4 Reflectance of transparent conductive film 1 for light with a wavelength of 1500 nm The reflectance of the transparent conductive film 1 to light having a wavelength of 1500 nm is, for example, 40% or more, preferably 45% or more, more preferably 47% or more, even more preferably 50% or more, particularly preferably 51% or more, and most preferably 52% or more. If the reflectance of the transparent conductive film 1 to light having a wavelength of 1500 nm is equal to or more than the above-mentioned lower limit, the transparent conductive film 1 has excellent infrared ray shielding (cutting) properties, and is suitably used as an infrared ray cut film.

[0049] There is no upper limit to the reflectance of the transparent conductive film 1 for light with a wavelength of 1500 nm. The upper limit to the reflectance of the transparent conductive film 1 for light with a wavelength of 1500 nm is, for example, 100%.

[0050] 1.5 Thickness and other physical properties of transparent conductive film 1 The transparent conductive film 1 has a thickness of, for example, 2 μm or more, preferably 20 μm or more, more preferably 30 μm or more, and for example, 300 μm or less, preferably 200 μm or less, more preferably 100 μm or less.

[0051] The transparent conductive film 1 has a total light transmittance of, for example, 75% or more, preferably 80% or more, and for example, 100% or less.

[0052] 1.6 Manufacturing method of transparent conductive film 1 In this method, for example, each of the layers is laid down in a roll-to-roll process.

[0053] 1.6.1 Preparation of substrate 2 First, a long substrate 2 is prepared. Specifically, a first curable composition and a second curable composition are applied to one side and the other side of a long substrate sheet 21, respectively. Then, the curable resin in each of the first curable composition and the second curable composition is cured by heat or ultraviolet light irradiation. In this way, an optical adjustment layer 22 and a hard coat layer 23 are formed on one side and the other side of the substrate sheet 21, respectively. In this way, the substrate 2 is prepared.

[0054] 1.6.2 Formation of crystalline transparent conductive layer 3 Thereafter, the crystalline transparent conductive layer 3 is formed on one surface in the thickness direction of the substrate 2. Specifically, first, an amorphous transparent conductive layer 31 (see the symbols in parentheses in FIG. 1) is formed on one surface in the thickness direction of the substrate 2, and then the amorphous transparent conductive layer 31 is converted to a crystalline material to form the crystalline transparent conductive layer 3.

[0055] 1.6.2.1 Formation of the amorphous transparent conductive layer 31 To form the amorphous transparent conductive layer 31, for example, sputtering, preferably reactive sputtering, is carried out.

[0056] In the sputtering, a sputtering device is used, which includes a film-forming roll.

[0057] In sputtering (preferably reactive sputtering), the above-mentioned metal oxide (sintered body) is used as a target.

[0058] In the sputtering, a sputtering gas is used. The sputtering gas may be a rare gas having an atomic number greater than that of argon. Examples of rare gases having an atomic number greater than that of argon include krypton, xenon, and radon, and preferably krypton (Kr). The sputtering gas preferably does not contain argon.

[0059] The sputtering gas is preferably mixed with a reactive gas. The reactive gas may be, for example, oxygen. The ratio of the amount of reactive gas introduced to the total amount of sputtering gas and reactive gas introduced is, for example, 0.1% by flow or more, preferably 0.5% by flow or more, and, for example, 5.0% by flow or less, preferably 3.5% by flow or less, more preferably 3.3% by flow or less, even more preferably 3.1% by flow or less, particularly preferably 3.0% by flow or less, and most preferably 2.9% by flow or less. If the ratio of the amount of reactive gas introduced to the total amount of sputtering gas and reactive gas introduced is equal to or less than the above-mentioned upper limit, the carrier density in the crystalline transparent conductive layer 3 can be increased, and the reflectance of the transparent conductive film 1 to infrared rays can be increased.

[0060] The air pressure inside the sputtering apparatus is, for example, 1.0 Pa or less, and, for example, 0.01 Pa or more.

[0061] In this way, a laminate including the substrate 2 and the amorphous transparent conductive layer 31 is manufactured.

[0062] 1.6.2.2 Conversion of the amorphous transparent conductive layer 31 to a crystalline state Thereafter, the amorphous transparent conductive layer 31 is converted to a crystalline form to form a crystalline transparent conductive layer 3 .

[0063] To convert the crystalline transparent conductive layer 3 into a crystalline state, the crystalline transparent conductive layer 3 (or the laminate including the layer) is heated.

[0064] The heating temperature is, for example, 80° C. or more, preferably 110° C. or more, more preferably 130° C. or more, particularly preferably 150° C. or more, and for example, 200° C. or less, preferably 180° C. or less, more preferably 175° C. or less, and more preferably 170° C. or less. The heating time is, for example, 1 minute or more, preferably 3 minutes or more, more preferably 5 minutes or more, and for example, 5 hours or less, preferably 3 hours or less, more preferably 2 hours or less.

[0065] The heating is performed, for example, in a vacuum or in the atmosphere. From the viewpoint of further increasing the carrier density in the crystalline transparent conductive layer 3 and further increasing the reflectivity of the transparent conductive film 1 to infrared rays, the heating is preferably performed in a vacuum.

[0066] Alternatively, the transparent conductive film 1 having the crystalline transparent conductive layer 3 can be left in the atmosphere at a temperature in the range of 20°C or higher and lower than 80°C for, for example, 10 hours or more, preferably 24 hours or more, to convert the crystalline transparent conductive layer 3 to a crystalline state.

[0067] 1.7 Applications of Transparent Conductive Film 1 The transparent conductive film 1 is used in, for example, articles. Examples of the articles include optical articles. More specifically, examples of the articles include touch sensors, electromagnetic wave shields, light control elements, photoelectric conversion elements, heat ray control members, light-transmitting antenna members, light-transmitting heater members, image display devices, and lighting.

[0068] Preferably, the transparent conductive film 1 is used as an infrared reflective film (or an infrared cut film).

[0069] 2. Effects of one embodiment This transparent conductive film 1 has a crystalline transparent conductive layer 3 instead of the metal layer described in Patent Document 1, and therefore has excellent corrosion resistance.

[0070] In addition, in the transparent conductive film 1, the carrier density of the crystalline transparent conductive layer 3 is 13.0×10 20 ( / cm 3 ), the amount of carriers that can contribute to the reflection of infrared rays is large. Therefore, the transparent conductive film 1 has high reflectance to infrared rays.

[0071] Furthermore, in this transparent conductive film 1, the crystalline transparent conductive layer 3 is an inorganic oxide layer and does not contain an elemental metal, and therefore has excellent corrosion resistance.

[0072] 3. Modifications In the following modifications, the same components and steps as those in the above-described embodiment are denoted by the same reference numerals, and detailed description thereof will be omitted. In addition, each modification can achieve the same effects as those in the above-described embodiment, unless otherwise specified. Furthermore, the embodiment and the modifications can be appropriately combined.

[0073] In a modified example (not shown), the functional layer 20 is disposed on one side or the other side of the base sheet 21 in the thickness direction. The functional layer 20 may be either a hard coat layer or an optical adjustment layer. In other words, one or more functional layers 20 are disposed on one side and / or the other side of the base sheet 21 in the thickness direction. EXAMPLES

[0074] The present invention will be described in more detail below with reference to examples. Note that the present invention is not limited to the examples. In addition, the specific numerical values ​​of the blending ratio (content ratio), physical property values, parameters, etc. used in the following description can be replaced with the upper limit (a numerical value defined as "not more than" or "less than") or lower limit (a numerical value defined as "not less than" or "exceeding") of the corresponding blending ratio (content ratio), physical property values, parameters, etc. described in the above "Form for carrying out the invention".

[0075] <Example 1> A long substrate 2 was prepared. Specifically, a roll of substrate 2 (manufactured by Mitsubishi Chemical Corporation, product name: GF-50JBN) having a thickness of 52 μm was prepared, the roll including a substrate sheet 21 made of PET, an optical adjustment layer 22 disposed on one surface of the substrate 2 in the thickness direction, and a hard coat layer 23 disposed on the other surface of the substrate 2 in the thickness direction.

[0076] An amorphous transparent conductive layer 31 having a thickness of 145 nm was formed by reactive sputtering on one surface of the substrate 2. In the reactive sputtering, the above-mentioned roll body was set in a DC magnetron sputtering device, and while the substrate 2 was being unwound from the roll body, the amorphous transparent conductive layer 31 was continuously formed on one surface of the substrate 2, thereby producing a laminate including the substrate 2 and the amorphous transparent conductive layer 31 in order toward one side in the thickness direction.

[0077] The sputtering conditions were as follows: A sintered body of indium oxide and tin oxide was used as a target. The tin oxide concentration in the sintered body was 10 mass %. A voltage was applied to the target using a DC power source. The horizontal magnetic field strength above the target was 90 mT. The ultimate vacuum in the film formation chamber of the DC magnetron sputtering device was 0.9×10 -4The film formation chamber was evacuated to a vacuum until the pressure reached 0.2 Pa, and a degassing process was performed on the substrate 2. Thereafter, Kr as a sputtering gas and oxygen as a reactive gas were introduced into the film formation chamber, and the pressure in the film formation chamber was set to 0.2 Pa. The ratio of the amount of oxygen introduced to the total amount of Kr and oxygen introduced into the film formation chamber was approximately 3.1 flow rate %.

[0078] Thereafter, the laminate was heated in a hot air oven at 160° C. in the atmosphere, whereby the amorphous transparent conductive layer 31 was converted to a crystalline state, and a crystalline transparent conductive layer 3 was formed.

[0079] In this way, a transparent conductive film 1 was produced which was provided with the substrate 2 and the amorphous transparent conductive layer 31 in that order towards one side in the thickness direction.

[0080] <Examples 2 to 4 and Comparative Examples 1 to 3> Transparent conductive film 1 was produced in the same manner as in Example 1. However, the type of rare gas in the sputtering gas, the ratio of the amount of oxygen introduced, and / or the atmosphere during heating were changed as shown in Table 1.

[0081] Specifically, in the column "Atmosphere during heating" in Examples 2 to 4, "vacuum" indicates that the laminate having the amorphous transparent conductive layer 31 laminated thereon was not wound up on a roll, but was transported in a vacuum while being in contact with a heating roll at 160° C. In other words, the amorphous transparent conductive layer 31 was heated in a vacuum in a sputtering apparatus.

[0082] 2, in Comparative Example 1, a transparent conductive layer 32 including a first inorganic oxide layer 33, a metal layer 34, and a second inorganic oxide layer 35 in that order on one side in the thickness direction was provided on a transparent conductive film 1. The transparent conductive layer 32 was formed as follows.

[0083] A first inorganic oxide layer 33 made of ITO and having a thickness of 40 nm was formed on one surface of the substrate 2 in the thickness direction by a reactive sputtering method. The method for forming the first inorganic oxide layer 33 was the same as that for forming the amorphous transparent conductive layer 31 in Example 1. However, Ar was used as the sputtering gas, and the ratio of the amount of oxygen introduced to the total amount of Ar and oxygen introduced into the film formation chamber was changed to 3.8 flow rate %.

[0084] A metal layer 34 made of an Ag alloy and having a thickness of 8 nm was formed on one surface of the first inorganic oxide layer 33 in the thickness direction by sputtering. Specifically, an Ag alloy target (manufactured by Mitsubishi Materials Corporation, product number "No. 317") was sputtered in a vacuum atmosphere at a pressure of 0.4 Pa into which Ar was introduced.

[0085] A second inorganic oxide layer 35 made of ITO and having a thickness of 38 nm was formed on one surface of the metal layer 34 in the thickness direction by a reactive sputtering method. The method for forming the second inorganic oxide layer 35 was the same as that for forming the amorphous transparent conductive layer 31 in Example 1. However, Ar was used as the sputtering gas, and the ratio of the amount of oxygen introduced to the total amount of Ar and oxygen introduced into the film formation chamber was changed to 3.8 flow rate %.

[0086] The first inorganic oxide layer 33 and the second inorganic oxide layer 35 in the transparent conductive layer 32 are both amorphous.

[0087] In Comparative Example 3, the amorphous transparent conductive layer 31 was not converted to a crystalline state.

[0088] <Evaluation> The transparent conductive films 1 of the respective Examples and Comparative Examples were evaluated for the following items.

[0089] (1) Carrier density of transparent conductive layer The carrier density of the transparent conductive layer was measured using a Hall effect measurement system (product name "HL5500PC", manufactured by Bio-Rad).

[0090] (2) Reflectance of the transparent conductive film for light at 1500 nm The reflectance of the transparent conductive film 1 to light with a wavelength of 1500 nm was measured using a spectrophotometer U4100 (manufactured by Hitachi, Ltd.) Specifically, an adhesive layer (manufactured by Nitto Denko Corporation) was attached to the other surface of the transparent conductive film 1 in the thickness direction, and a black acrylic plate was further attached to the other surface of the adhesive layer in the thickness direction, and the reflectance of the transparent conductive film 1 to light with a wavelength of 1500 nm was measured.

[0091] (3) Corrosion resistance The transparent conductive film 1 was cut into a size of 10 cm x 10 cm. The transparent conductive film 1 was then placed in a high-temperature, high-humidity chamber at 60°C and 95% RH for 240 hours. The appearance of one side of the transparent conductive film 1 in the thickness direction (the surface of the crystalline transparent conductive layer 3) was then observed. Specifically, an 8 cm x 8 cm area in the center was visually observed. The corrosion resistance was evaluated based on the following criteria.

[0092] ◯: No white dot-like defects due to corrosion were observed, i.e., the number of defects was 0. △: 1 to 4 white dot-like defects due to corrosion were observed. ×: Five or more white dot-like defects due to corrosion were observed.

[0093] (4) Surface resistance of the transparent conductive layer The surface resistance of the transparent conductive layer was measured by the four-terminal method in accordance with JIS K7194 (1994).

[0094] (5) Confirmation of Kr in the transparent conductive layer The presence or absence of Kr in the transparent conductive layer was confirmed as follows.

[0095] First, using a scanning X-ray fluorescence analyzer (product name "ZSX PrimusIV", manufactured by Rigaku Corporation), X-ray fluorescence analysis was repeated five times under the following measurement conditions, and the average value of each scanning angle was calculated to create an X-ray spectrum. Then, in the created X-ray spectrum, it was confirmed that a peak appeared near a scanning angle of 28.2° in Examples 1 to 4 and Comparative Example 3.

[0096] On the other hand, in Comparative Examples 1 and 2, it was confirmed that the above-mentioned peak did not appear.

[0097] <Measurement conditions> Spectrum;Kr-KA Measurement diameter: 30mm Atmosphere: Vacuum Target: Rh Tube voltage: 50kV Tube current: 60mA Primary filter: Ni40 Scanning angle (deg): 27.0~29.5 Step(deg):0.020 Speed ​​(deg / min): 0.75 Attenuator: 1 / 1 Slit: S2 Spectroscopic crystal: LiF(200) Detector: SC PHA: 100~300

[0098] (6) Confirmation of Ar in the transparent conductive layer It was confirmed by Rutherford backscattering spectroscopy (RBS) that none of the transparent conductive layers in Examples 1 to 4 and Comparative Example 3 contained Ar, and that both of the transparent conductive layers in Comparative Examples 1 and 2 contained Ar.

[0099] Specifically, the presence or absence of Ar was confirmed by measuring four elements: In+Sn (since it is difficult to measure In and Sn separately using Rutherford backscattering spectrometry, the two elements were evaluated as a combined value), O, and Ar. The equipment and measurement conditions used are as follows:

[0100] <Equipment used> Pelletron 3SDH (manufactured by National Electrostatics Corporation)

[0101] <Measurement conditions> Incident ion: 4He++ Incident energy: 2300keV Incident angle: 0deg Scattering angle: 160deg Specimen current: 6nA Beam diameter: 2mmφ In-plane rotation: None Irradiation dose: 75μC

[0102] [Table 1]

[0103] The above invention is provided as an exemplary embodiment of the present invention, but this is merely an example and should not be interpreted as being limited. Modifications of the present invention that are obvious to those skilled in the art are included in the scope of the following claims. [Industrial Applicability]

[0104] The transparent conductive film is used in optical articles. [Explanation of symbols]

[0105] 1. Transparent conductive film 2 Base material 3. Crystalline transparent conductive layer

Claims

1. A substrate and a crystalline transparent conductive layer are provided in this order toward one side in a thickness direction, the crystalline transparent conductive layer contains a rare gas having an atomic number greater than that of argon, The carrier density of the crystalline transparent conductive layer is 13.0×10 20 ( / cm 3 ) or higher.

2. The transparent conductive film according to claim 1 , wherein the crystalline transparent conductive layer is an inorganic oxide layer.

Citation Information

Patent Citations

  • Forming method of indium / Tin oxide transparent conductive film

    JP1997078236A

  • Low resistance ITO thin film and its preparation

    JP2001089846A

  • Manufacture of transparent conductive film

    JP1993334924A